Answer:
[tex]y=\frac{11}{5}[/tex]
Step-by-step explanation:
Given expression
[tex]\frac{1}{3}(y-2)-\frac{5}{6}(y+1)=\frac{3}{4}(y-3)-2[/tex]
To solve for [tex]y[/tex] for the given expression.
Solution:
We multiply each term with the least common multiple of the denominators of the fraction in order to remove fractions.
The multiples of the denominators are:
3 = 3,6,9,12,15
6 = 6,12
4 = 4,8,12
The least common multiple = 12.
Multiplying each term with 12.
[tex]12.\frac{1}{3}(y-2)-12.\frac{5}{6}(y+1)=12.\frac{3}{4}(y-3)-2(12)[/tex]
[tex]4(y-2)-10(y+1)=9(y-3)-24[/tex]
Using distribution.
[tex]4y-8-10y-10=9y-27-24[/tex]
Simplifying.
[tex]-6y-18=9y-51[/tex]
Adding [tex]6y[/tex] both sides.
[tex]-6y+6y-18=9y+6y-51[/tex]
[tex]-18=15y-51[/tex]
Adding 51 both sides.
[tex]-18+51=15y-51+51[/tex]
[tex]33=15y[/tex]
Dividing both sides by 15.
[tex]\frac{33}{15}=\frac{15y}{15}[/tex]
[tex]\frac{33}{15}=y[/tex]
Simplifying fractions.
[tex]\frac{11}{5}=y[/tex]
∴ [tex]y=\frac{11}{5}[/tex] (Answer)